Capsule endoscopy aspiration and respiratory physician’s treatment insights: a case report and literature review - Zhou, Yinxue; Wang, Hongmei; Zhuang, Min; Liu, Hua; Qi, Lijie; Zhang, Lingyun; Sun, Jiaxing (Frontiers in Medicine, 2024)
Background： Capsule endoscopy (CE) is widely used for intestinal examination, but capsule aspiration into the airway is a serious complication needing urgent intervention. We present a management case and review 39 cases from 2003 to 2023, providing insights into prevention and treatment of capsule aspiration.Case Presentation: A 69-year-old male with chronic bronchitis and emphysema, presenting with 7 months of intermittent melena, experienced brief coughing and chest tightness after swallowing a capsule endoscope (PillCam™ SB 3). Imaging confirmed aspiration in the right intermediate bronchus, and non-invasive removal attempts were unsuccessful.Methods: Real-time imaging confirmed the lodged capsule. Non-invasive methods like coughing and chest percussion failed, so flexible bronchoscopy under general anesthesia was used to retrieve the capsule with a snare, followed by placement into the duodenum via gastroscope.The capsule was successfully retrieved, and the patient recovered well, completing the endoscopy without further issues.Conclusion：Our case and literature review highlight the need for careful attention to highrisk groups in CE, including the elderly and those with neurological or swallowing issues, with thorough history review and real-time monitoring essential. Bronchoscopy is preferred for CE retrieval due to its advantages, and manufacturers are urged to improve CE safety, with insights from respiratory physicians to help internists manage this potentially life-threatening complication.